2014
DOI: 10.1063/1.4900942
|View full text |Cite
|
Sign up to set email alerts
|

Size-tunable strain engineering in Ge nanocrystals embedded within SiO2 and Si3N4

Abstract: We report a unique ability to control the sign and size of the stress within Ge nanocrystals or nanodots fabricated using a complementary metal-oxide-semiconductor-compatible process within SiO2 and Si3N4 layers. Very large (as much as 4.5%), size-dependent compressive and tensile strains can be generated depending on whether the dot is embedded within either a Si3N4 or a SiO2 layer. Raman measurements reveal significant anharmonicity for smaller Ge dots and possible distortions of the diamond cubic lattice as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…In summary, the thicker Si1−xGex shells resulting from the larger Ge dots have shown us that Ge diffusion lengths in Si calculated using conventional formulas may have to be revised in light of the observed Ge-catalyzed Si vacancy enhancement. In addition to excellent crystallinity confirmed by the clear lattice fringes observed in the high-resolution TEM micrographs and SADs, our previous work (Liao et al, 2014) on the Raman characterization of the SiGe-shell region has shown a large blue shift of the longitudinal optical Ge-Ge phonon line (309 cm −1 from the SiGe shell as opposed to the 301 cm −1 for bulk Ge). This blue shift suggests the SiGe shell is being subjected to a compressive strain of ~1.6% and is therefore in reasonable agreement with the SAD analysis from Figure 4C.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In summary, the thicker Si1−xGex shells resulting from the larger Ge dots have shown us that Ge diffusion lengths in Si calculated using conventional formulas may have to be revised in light of the observed Ge-catalyzed Si vacancy enhancement. In addition to excellent crystallinity confirmed by the clear lattice fringes observed in the high-resolution TEM micrographs and SADs, our previous work (Liao et al, 2014) on the Raman characterization of the SiGe-shell region has shown a large blue shift of the longitudinal optical Ge-Ge phonon line (309 cm −1 from the SiGe shell as opposed to the 301 cm −1 for bulk Ge). This blue shift suggests the SiGe shell is being subjected to a compressive strain of ~1.6% and is therefore in reasonable agreement with the SAD analysis from Figure 4C.…”
Section: Discussionmentioning
confidence: 95%
“…Also, the appearance of a weak Raman signal at 406-414 cm −1 suggests that the chemical composition of the Si1−xGex shell has a strong dependence on the dot size. The Ge mole fraction is as high as x = 0.55-0.72 for the SiGe shells formed from 50 to 90 nm Ge dots (Pezzoli et al, 2008;Liao et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Below the interfacial oxide layer, an approximately 20-nm-thick Si 1- x Ge x shell is generated within the Si substrate. A substantial amount ( x  ≈ 0.72) of Ge as estimated from the Raman signal at 414 cm −1 for the SiGe shells formed from the 90-nm Ge QDs [21, 22]. Clear lattice fringes are observed in the high-resolution CTEM micrographs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, reducing the Ge dot size from 90 nm to 50 nm leads to an improvement in both normalized ON and OFF per unit Ge volume by a factor of 2.75 for Ge-dot PTs under both low- and high-power 850 nm illumination conditions. The improved IQE for the smaller Ge dots is possibly due to a significant improvement in crystallinity quality with reduced defect densities and an increased strain20, leading to better photoelectric conversion efficiency. As the nanodots get bigger, the statistical probability of having crystalline defects such as dislocations increases.…”
Section: Discussionmentioning
confidence: 99%